Hacking exposed : - McClure, Stuart (Osborne/McGraw-Hill, 1999)
Systems administrators are often unaware of the dangers presented by anything beyong the most trivial attacks. Because of the day-to-day tasks, Y2K projects, and increasingly complex technology, administrators have perpetually back-burnerer security issues out of necessity. However, recent high-profile viruses and events like the White House website being closed down by hackers has brought the issue back to the forefront. With Hacking Exposed: Network Security Secrets and Solutions, Osborne will provide administrators with a modular and approachable reference so they can select the most pertinent information, rapidly digest it, and apply it immediately